Biorremediação de herbicidas em água do cultivo de arroz irrigado visando minimizar o impacto ambiental - Roehrs, Rafael (2008)
Irrigated rice production depends on the pesticides application, among other factors. Herbicides could be highlighted as the most used ones, which may be transported into natural water sources, generating pollution and risk to the environment and to the human beings health. The genetic improvement along with cultivation techniques optimization and use of pesticides to control plagues are alternatives to increase rice productivity. However, the intensive use of pesticides generates a greater environmental impact, turning the natural pesticides degradation even slower. In order to develop an economically viable process for irrigated rice fields water bioremediation, a bacterium strain from the soil with history of pesticides use has been isolated, being the influence of different conditions in degradation efficiency evaluated. The process consists in isolating a microorganism from the soil, utilizing selective medium incubation for the target herbicides. After isolating and selecting, through biodegradation assays, the possible microorganism with degradation potential, it was identified by the University de la Republica (Montevideo-Uruguay). Aiming to observe closely the degradation potential of strain RR02, it was utilized an HPLC-UV system with stationary phase Synergi Fusion RP-80, mobile phase acetonitrile:methanol:water (30:24:46, v/v; pH 3.0), flow rate of 0.8 mL min-1 and detection in 220 nm. The influence of the growth phase, the incubation temperature and the conditions of high and low oxygenation of the medium during a 30-day period was assessed utilizing a mineral culture medium with the herbicides. The results show that the strain RR02 has a good capability to degrade the studied herbicides. Since each herbicide has been separately evaluated, it was possible to notice a decrease between 50 and 100% in the initial concentration. During the herbicides mixture evaluation the biodegradation was lower, or almost null, considering the conditions without aeration of the medium. The medium aeration can improve the herbicides degradation when they are in a mixture. The least satisfactory degradation results happened during the microorganism stationary growth phase, with little or no degradation at all. This strain supports up to 10 times the doses used in the rice farming, showing a decline from 30 to 100% for the highest dose in 28 days. When this strain is compared to commercial products, the results are similar or even higher, because it used a smaller number of cells of the strain RR02 than those provided by commercial products. The synergistic effect of two processes of bioremediation the microbial bioremediation and phytoremediation were assessed and displayed that the combination produces better results than each of the processes of remediation alone. The use of microorganisms in the environment bioremediation is efficient and economically viable, since it is not necessary the application of any type of chemicals or equipment that could multiply the cost of rice production. The environmental impact should not be ignored; however, the fact that the microorganisms used in the research are actually from the cultivation area considerably minimizes the impact.